Coating of Mesh Grafts for Prolapse and Urinary Incontinence Repair with Autologous Plasma: Exploration Stage of a Surgical Innovation. (16th September 2014) - Barski, Dimitri; Gerullis, Holger; Georgas, Evangelos; Bär, Andreas; Lammers, Bernhard; Ramon, Albert; Ysebaert, Dirk; Klosterhalfen, Bernd; Boros, Mihaly; Otto, Thomas
Abstract : Purpose . Optimized biocompatibility is a major requirement for alloplastic materials currently applied for stress urinary incontinence (SUI) and pelvic organ prolapse (POP) repair. In the preliminary studies the mesh modification by coating with autologous plasma resulted in the increased adherence score in vitro and improved biocompatibility in an animal model. The first use of plasma coated meshes in human is presented. Materials and Methods . Between 04/2013 and 05/2014, 20 patients with the indication for SUI and POP repair were selected in a single institution. The applied meshes were modified by autologous plasma coating prior to implantation. A retrospective chart review for peri- and early postoperative complications was performed. Functional outcome and QoL were evaluated pre- and postoperatively. Results . The functional outcome and QoL improved significantly in all groups. Two reoperations (Grade IIIB) with the release of TVT-mesh in anesthesia due to the obstruction were needed. No other severe complications were registered. Conclusion . For the first time we applied a mesh modification in a human setting according to IDEAL criteria of surgical innovations. The procedure of mesh coating with autologous plasma is safe and a prospective randomized trial proving a positive effect of plasma coating on the biocompatibility and morbidity outcome with long-term registry is planned.